Prioritize Strategies to Address the Sustainable Supply Chain Innovation Using Multicriteria Decision-Making Methods - Mahmonir Bayanati; Ali Peivandizadeh; Mohamad Reza Heidari; Sadegh Foroutan Mofrad; Mohammad Reza Sasouli; Adel Pourghader Chobar (Complexity)
Today, due to the increase in people’s awareness of environmental issues and the strict policies of governments, the competitiveness of companies depends on considering environmental issues at all levels of the supply chain. However, the implementation of green supply chain management strategies has lots of different risks. The main contribution of this research is to evaluate and rank the companies in the tire industry with an emphasis on the environmental risks of the sustainable supply chain using the hybrid best-worst method (BWM) and fuzzy VIKOR (FVIKOR). First, data analysis was implemented by applying the BWM technique, which has higher reliability than other similar techniques. Next, the importance of the indicators involved in the risk of the green supply chain, including operational, supply, product return, financial, demand, organizational, and government, was calculated. Finally, according to the calculated weights for each criterion, five active companies in the tire industry were ranked using the FVIKOR technique. The results of prioritizing criteria and subcriteria showed that “financial risks” are the most important indicator among the indicators involved in green supply chain risk. Among the subcriteria, “rates related to inflation and currency” from the cluster of financial risks were recognized as the most important subcriteria. Moreover, the results of the ranking of five companies in the tire industry indicated that Dana Company is in the best situation in terms of green supply chain risks. Finally, a series of practical suggestions for managers and a series of scientific suggestions for future research have been presented.